2017
DOI: 10.1037/abn0000291
|View full text |Cite
|
Sign up to set email alerts
|

Taxometric analyses of pedophilia utilizing self-report, behavioral, and sexual arousal indicators.

Abstract: Pedophilia refers to the recurrent, intense sexual interest in prepubescent children who, by definition, have not developed any secondary sex characteristics. Researchers have begun to investigate whether persons with pedophilia are qualitatively different from those without pedophilia (pedophilia is a taxon) or if people vary in their level of sexual interest toward children (pedophilia is dimensional). Two relatively small studies have previously attempted to address this question, but produced conflicting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…Recent taxometric research has found pedophilic interest to be taxonic (Brankley, 2019; McPhail et al, 2018; Schmidt et al, 2013) and dimensional (Stephens et al, 2017). The main meta-analyses that we conducted model pedohebephilic interest as a dimension.…”
Section: Methodsmentioning
confidence: 99%
“…Recent taxometric research has found pedophilic interest to be taxonic (Brankley, 2019; McPhail et al, 2018; Schmidt et al, 2013) and dimensional (Stephens et al, 2017). The main meta-analyses that we conducted model pedohebephilic interest as a dimension.…”
Section: Methodsmentioning
confidence: 99%
“…The use of clinical assessment data for research purposes was approved by the institutional research ethics board. This archival database has been used in previous studies examining different research questions about the assessment of sexual interest in children and the validity of various assessment measures used at the clinic (Barbaree, Blanchard, & Langton, 2003; Blanchard 2011; Blanchard & Barbaree, 2005; Blanchard, Kuban, et al, 2009; Blanchard, Lykins, et al, 2009; Blanchard et al, 2001; 2006, 2007, 2012; Cantor & McPhail, 2015; Lykins et al, 2010; Seto, Cantor, & Blanchard, 2006; Seto, Stephens, et al, 2017; Stephens, Leroux, Skilling, Cantor, & Seto, 2017; Stephens, Seto, Goodwill, & Cantor, 2017, 2018; Stephens et al, 2019). The database is not publicly available because it contains sensitive clinical data and there is a potential risk that participants could be identified by triangulation of data.…”
Section: Methodsmentioning
confidence: 99%
“…xuelles Interesse an Kindern, die per definitionem noch keine sekundären Geschlechtsmerkmale entwickelt haben (Seto 2009;Stephens et al 2017). Dabei wird u. a. zwischen exklusiver und nichtexklusiver Pädophilie unterschieden.…”
Section: Unter Pädophilie Versteht Man Ein Intensives Und Anhaltendesunclassified
“…Bei einer nicht-exklusiven Pädophilie kann sich der Betroffene hingegen auch zu Erwachsenen sexuell hingezogen fühlen (APA 2013). Das Ausmaß des sexuellen Interesses an Kindern ist individuell unterschiedlich, sodass Pädophilie auch als dimensionales Konstrukt mit unterschiedlichen Ausprägungsgraden verstanden werden kann (Mackaronis et al 2011;Stephens et al 2017).…”
Section: Unter Pädophilie Versteht Man Ein Intensives Und Anhaltendesunclassified